SPA DAY VERSION 3: PROPOSED UPGRADED COURSE AND CLASSROOM SCHEDULING IN CTU FOR DAY CLASSES - Mondejar, Jeremy P. (Journal of Agriculture and Technology Management, 2018)
Schedule Programming Assistant (SPA) for day classes was upgraded to farther reduce memory requirement and enhance its capabilities. SPADay version 3 was restructured into six (6) workbooks mainly (1) Consolidated_Schedules_Database, (2) Faculty_Profiles, (3) Subject_codes, (4) SPADay_Department, (5) SPADay_consolidated, and (6) SPADay_INS. SPA_Department can be replicated  according  to  the  number  of  academic  departments  in  the  campus  since  class scheduling in CTU is done by department. SPADay version 3, an excel template, requires Windows operating system, at least with 1 GB RAM in Microsoft Excel 2007. These have VBA macros for checking data that will cause run-time error, determining conflicts in faculty loads and room utilization, determining over-loaded and under-loaded faculty, (d) number of preparations, units, hours of classes per week, and summary of schedules. Finally, SPA-INS templates were created in a separate workbook for producing pictographic chart of schedules by teacher, schedules by section, and room utilization as final outputs in course timetabling.